Tauhid As Knowledge Base and Integration of Knowledge in The Reform of Islamic Education in Lombok: Study of The Thought and Role of Tuan Guru Haji Ibrahim Al-Khalidy - Muhammad Muhlis; Masnun Masnun; Lalu Zainal Arifin; Lalu Ahmad Zainuri (Jurnal Iqra': Kajian Ilmu Pendidikan)
This article explores the educational reform ideas of Tuan Guru Ibrahim Al-Khalidy, a key figure in the development of Islamic education in Lombok. As the founder of the Al-Ishlahuddiny Islamic Boarding School, TGH Ibrahim Al-Khalidy has successfully combined traditional pesantren education with modern educational systems. This reform was designed to preserve the pesantren as a center for the production of ulama while adapting to the challenges of modernization and contemporary Islamic education management. Using a qualitative research methodology with a field research approach, data was gathered through observation, documentation, and interviews. The findings reveal that TGH Ibrahim Al-Khalidy's educational reform is deeply rooted in the concept of tauhid and the integration of knowledge, which is prominently reflected in his work Tuhfatu al-Shibyan Fii Aqo`idil Iman. His approach advocates for a holistic Islamic education that encompasses both religious and general knowledge, fostering a balanced development of students. The research further demonstrates that his educational reform has made significant contributions to the social and cultural development of the community, bridging the gap between traditional Islamic teachings and contemporary educational needs.